Prevalence and molecular identification of protozoan intestinal parasitic infections in cancer patients and a control group - Leyla Bahadorizadeh; Khadijeh Khanaliha; Saeede Ghorbandoust; Farah Bokharei-Salim; Sara Minaeian; Nastaran Khodakarim; Marzieh Ghalamkari; Borna Salemi (BMC Infectious Diseases)
Abstract Background Parasitic infections, especially opportunistic infections, are important issues for immunocompromised patients, including cancer patients. In this study, the prevalence of intestinal protozoan infections was investigated in Iranian cancer patients and a control group using microscopic and molecular methods. Methods This cross-sectional study was conducted on a group of 158 individuals with gastrointestinal and non-gastrointestinal cancers from hospitals affiliated with the Iran University of Medical Sciences, alongside 158 healthy individuals included in the control group. Stool samples were collected and examined using direct and concentration methods. The modified acid-fast staining method was used to detect coccidian parasite infections. DNA was extracted from the patients’ samples, and PCR and sequencing were performed. Results The overall prevalence of protozoan infections was higher in the cancer patients (31.6%) than in the control group (12.0%), with the difference between the two groups being statistically significant (P = 0.0001). The study identified Blastocystis hominis as the most common protozoan, with a prevalence of 22.8%, followed by Giardia lamblia, Entamoeba coli, Dientamoeba fragilis, and Chilomastix mesnili, with rates of 2.5%, 1.3%, 1.3%, and 0.6%, respectively, in the cancer patients. Cystoisospora belli and Cryptosporidium sp. were found as opportunistic infections in 2.5% and 0.6% of the cancer patients, respectively. Blastocystis hominis, with a prevalence of 9.5%, followed by Giardia lamblia at 1.3%, were the most common parasitic infections in the control group. A statistical difference was found for Cystoisospora belli (P = 0.044) and Blastocystis hominis (P = 0.0013) between the cancer patients and the control group. Cryptosporidium sp. was confirmed as Cryptosporidium parvum, and Cystoisospora belli was confirmed by PCR sequencing. Conclusion Chemotherapy, aside from corticosteroids, increases susceptibility to intestinal Protozoan infections in patients with hematological malignancies, particularly those with lymphoma and leukemia. The results indicated a higher risk of intestinal Protozoan infections, including opportunistic infections, in the cancer patients than in the control group. Cystoisospora belli and Cryptosporidium parvum were found to cause diarrhea in hematological malignancy patients undergoing chemotherapy.